ANALYSIS OF CAREER DEVELOPMENT, COMPETENCIES AND WORK DISCIPLINE ON MEDIATED EMPLOYEE PERFORMANCE JOB SATISFACTION IN THE SOCIAL SERVICE NORTH SUMATRA PROVINCE - Rahmayusiah; M. Chaerul Rizky (RADJA PUBLIKA, 2024)
The background of this research is based on the importance of improving employee performance in supporting social services to the community, during human resource challenges that continue to develop. The research method uses a quantitative approach with data collection techniques through questionnaires with a research population of 377 people, consisting of 264 ASN and 113 Non-ASN. The data was analyzed using Structural Equation Modeling based on Partial Least Squares. The results of the study show that career development, competence, and work discipline have a positive effect on employee performance. The research population is 377 people, consisting of 264 ASN and 113 Non-ASN. Job satisfaction has been proven to mediate the relationship between the two variables, namely career development and work discipline on employee performance. Pre-survey identification shows that career path understanding, training participation, and access to promotions are still the main obstacles in career development. In terms of competence, innovation and technology use still need to be improved. Meanwhile, in work discipline, compliance with work schedules shows realization that is still below the target. Career Development (X1) has a positive and significant effect on Employee Performance (Y), with a path coefficient value (Original Sample column) of 0.304, with a P-Values value = 0.000 (Accepted Hypothesis). Career Development (X1) has a positive and significant effect on Job Satisfaction (Z), with a path coefficient value (Original Sample column) of 0.233, with a value of P-Values = 0.000 (Accepted Hypothesis). Competency (X2) has a positive but not significant effect on Employee Performance (Y), with a path coefficient value (Original Sample column) of 0.134, with a P-Values value = 0.089 (Hypothesis Rejected because the significance value is above 0.05). Competency (X2) has a positive but insignificant effect on Job Satisfaction (Z), with a path coefficient value (Original Sample column) of 0.023, with a P-Values value = 0.697 (Hypothesis Rejected because the significance value is above 0.05). Job Satisfaction (Z) has a positive and significant effect on Employee Performance (Y), with a path coefficient value (Original Sample column) of 0.496, with a P-Values value = 0.002 (Accepted Hypothesis). Work Discipline (X3) has a positive but not significant effect on Employee Performance (Y), with a path coefficient value (Original Sample column) of 0.090, with a P-Values value = 0.435 (Hypothesis Rejected because the significance value is above 0.05). Work Discipline (X3) has a positive and significant effect on Job Satisfaction (Z), with a path coefficient value (Original Sample column) of 0.754, and significant, with a value of P-Values = 0.000 (Accepted Hypothesis). Job satisfaction (Z), significantly mediated the relationship between career development (X1) and employee performance (Y) with a P-Values value = 0.116 > 0.018 (Accepted Mediation Hypothesis). Job satisfaction (Z), insignificant mediated the relationship between competence (X2) and employee performance (Y), with a P-Values value = 0.012 < 0.712 (Hypothesis rejected because the significance value was above 0.05). Job satisfaction (Z), significantly mediated the relationship between work discipline (X3) and employee performance (Y), with a P-Values value = 0.374 > 0.002 (Accepted Mediation Hypothesis). This research makes a practical contribution in formulating effective human resource management strategies in the government sector.